INCIDENCE, RISK FACTORS, AND OUTCOME OF ACUTE KIDNEY INJURY AMONG CHILDREN IN PEDIATRIC INTENSIVE CARE UNIT IN A TERTIARY CARE HOSPITAL - M, Raja; P, Sivaprasath; P, Dhivya (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The study aimed to study the incidence, risk factors, outcome, and disease pattern of acute kidney injury (AKI) among children admitted in the pediatric intensive care unit (PICU). Methods: The present study was a prospective study done to study the incidence, risk factors, and outcome of AKI among children of the age group 1 month–12 years admitted in PICU at a tertiary care hospital. Results: A total of 480 PICU admissions were recruited, of which 276 children met the inclusion criteria. Of these, AKI was diagnosed in 119 children (50.4%) using pediatric risk, injury, failure, loss, and end-stage renal disease criteria, and the remaining 117 children were classified as non-AKI. The majority of children (63%) were in the age group of 5–12 years, and the male-to-female ratio was 1.2:1. From this study, it was recorded that the pathogenesis of AKI could be attributed to acute glomerulonephritis (AGN) (85%), sepsis (74%), and others like snake bite, diarrhea, poisoning cases, scorpion sting, diabetic ketoacidosis, heart failure, and unclassified causes with observable numbers. The most common offender is shock (91.4%) with vasopressor support (85.4%). Out of 82 children on inotropic support, 46 were on adrenaline. It was observed that the majority of children (93.5%) developed AKI during the course in hospital. The mortality rates were 64.7% and 24.5% among AKI and non-AKI patients. The mean duration of hospital stays among children without AKI was 5 days. Conclusion: The presence of AKI is associated with longer PICU and hospital stay, with higher mortality imposing a significant burden to health-care system.